1996
DOI: 10.1016/s0092-8674(00)80127-0
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ1 Inhibits the Formation of Benign Skin Tumors, but Enhances Progression to Invasive Spindle Carcinomas in Transgenic Mice

Abstract: TGFbeta1 has been implicated in cell cycle control and carcinogenesis. To address the exact function of TGFbeta1 in skin carcinogenesis in vivo, mice with TGFbeta1 expression targeted to keratinocytes were subjected to long-term chemical carcinogenesis treatment. TGFbeta1 showed biphasic action during multistage skin carcinogenesis, acting early as a tumor suppressor but later enhancing the malignant phenotype. The transgenics were more resistant to induction of benign skin tumors than controls, but the malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
424
0
4

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 586 publications
(451 citation statements)
references
References 65 publications
16
424
0
4
Order By: Relevance
“…TGF-b1 expression and endogeneous type II TGF-b receptor expression was present in the majority of early carcinomas derived from our dominant negative type II receptor transgenic mice. These results suggests that the carcinomas pro®t from tumor stimulating activities of TGF-b on stroma and angiogenesis (Roberts et al, 1986;FuÈ rstenberger et al, 1989;Cui et al, 1996;Oft et al, 1996). The malignant cells escape TGF-b mediated growth restriction due to the presence of the dominant negative type II receptor allowing for a very rapid growth of these lesions.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…TGF-b1 expression and endogeneous type II TGF-b receptor expression was present in the majority of early carcinomas derived from our dominant negative type II receptor transgenic mice. These results suggests that the carcinomas pro®t from tumor stimulating activities of TGF-b on stroma and angiogenesis (Roberts et al, 1986;FuÈ rstenberger et al, 1989;Cui et al, 1996;Oft et al, 1996). The malignant cells escape TGF-b mediated growth restriction due to the presence of the dominant negative type II receptor allowing for a very rapid growth of these lesions.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, it has been suggested that TGF-b plays an important role in skin carcinogenesis (Glick et Glick et al, 1994;Cui et al, 1996). To elucidate the function of TGF-b signaling in tumor development we subjected our transgenic mice to skin carcinogenesis protocols (DiGiovanni, 1991;Hennings et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cancer cells lacking particular Smad proteins, certain responses to TGF-b thus remain and may positively drive tumor progression. TGF-b may at this late stage of tumor progression function as a tumor promoter in a cell-autonomous manner by promoting tumor cell growth, migration and invasion (Cui et al, 1996;Oft et al, 1998). Furthermore, late stage tumor cells often produce high amounts of TGF-b, which, in a paracrine manner, may stimulate a favorable microenvironment for rapid tumor growth and metastasis by suppressing the immune system and stimulating angiogenesis and extracellular matrix formation .…”
Section: Introductionmentioning
confidence: 99%
“…Histological studies of bone metastases show that tumour cells remain in the bone marrow cavity and secrete factors that regulate bone cells including parathyroid hormone related protein (PTHrP), tumour necrosis factor (TNF), interleukin-6 (IL-6) and transforming growth factor (TGF)b (Yin et al, 2005). Among these local factors, serum TGFb was recently shown to be associated with disease progression and poor prognosis in patients with metastatic breast cancer (Cui et al, 1996;Sheen-Chen et al 2001;Ivanovic et al, 2003). Matrix-metalloproteases (MMPs) are a family of zincdependent endopeptidases, which degrade the extracellular matrix proteins.…”
mentioning
confidence: 99%